Health care network for children with zika virus from the perspective of professionals - Gleice Kelli Santana de Andrade; Sonia Silva Marcon; Adriane Pires Batiston; Eliane Tatsch Neves; Viviane Cazetta de Lima Vieira; Jennyfer Soares de Sá; Júnior Cezar de Souza Benedito; Elen Ferraz Teston (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To know the perspective of health professionals working in specialized care regarding the assistance offered to children with Congenital Zika Virus Syndrome in the Health Care Network. Method: Qualitative study carried out in Campo Grande-MS through semi-structured interviews, between September and October 2020, with 12 professionals working in a reference service for people with physical and intellectual disabilities. Minayo's thematic analysis and the theoretical subsidies of the care model for chronic conditions were used for interpretation. Results: Assistance in the network is weakened by aspects related to access, monitoring and integration between different professionals/services. The potential involves the implementation of the referral and counter-referral system, the communication/integration between these services and the training of professionals. Final considerations: The participants perceive that assistance is influenced by the availability of trained professionals to work in a network and the optimization of access and follow-up at different points of care.